IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN PENDEKATAN FUN LEARNING DALAM MENINGKATKAN KECERDASAN EMOSIONAL SISWA DI TAMAN PENDIDIKAN AL-QUR’AN FATURRAHMAN DESA TANGKIT BARU - Ikram, M.; Sya’roni; Amirul Mukminin Al-Anwari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of Islamic Religious Education (IRE) learning through the fun learning approach and its impact on students’ emotional intelligence at Taman Pendidikan Al-Qur’an (TPA) Faturrahman, Tangkit Baru Village. This research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing. The results show that the fun learning approach through playing, singing, storytelling, and educational games creates an enjoyable and participative learning atmosphere. It increases students’ motivation, activeness, and understanding of IRE materials. Furthermore, this approach contributes positively to the development of students’ emotional intelligence, including self-awareness, emotional control, empathy, cooperation, and social skills. The obstacles faced include limited learning media, short learning time, and differences in students’ abilities.